The Influence of Glutamate on Axonal Compound Action Potential In Vitro - Abouelela, Ahmed; Wieraszko, Andrzej (Journal of Brachial Plexus and Peripheral Nerve Injury, 2016)
Background Our previous experiments demonstrated modulation of the amplitude of the axonal compound action potential (CAP) by electrical stimulation. To verify assumption that glutamate released from axons could be involved in this phenomenon, the modification of the axonal CAP induced by glutamate was investigated.Objectives The major objective of this research is to verify the hypothesis that axonal activity would trigger the release of glutamate, which in turn would interact with specific axonal receptors modifying the amplitude of the action potential.Methods Segments of the sciatic nerve were exposed to exogenous glutamate in vitro, and CAP was recorded before and after glutamate application. In some experiments, the release of radioactive glutamate analog from the sciatic nerve exposed to exogenous glutamate was also evaluated.Results The glutamate-induced increase in CAP was blocked by different glutamate receptor antagonists. The effect of glutamate was not observed in Ca-free medium, and was blocked by antagonists of calcium channels. Exogenous glutamate, applied to the segments of sciatic nerve, induced the release of radioactive glutamate analog, demonstrating glutamate-induced glutamate release. Immunohistochemical examination revealed that axolemma contains components necessary for glutamatergic neurotransmission.Conclusion The proteins of the axonal membrane can under the influence of electrical stimulation or exogenous glutamate change membrane permeability and ionic conductance, leading to a change in the amplitude of CAP. We suggest that increased axonal activity leads to the release of glutamate that results in changes in the amplitude of CAPs.
Keywords: compound action potential; glutamate; axonal plasticity